Induction and Stabilization of Antibacterial Activity in a Bacillus subtilis 534 Probiotic Strain - O. V. Efremenkova; I. A. Malanicheva; B. F. Vasileva; T. A. Efimenko; A. A. Glukhova; O. V. Kisil; M. V. Demiankova; H. S. Semizaev; N. I. Gabrielyan (Антибиотики и Химиотерапия, 2022)
Medicinal probiotic Sporobacterin is based on the Bacillus subtilis 534 strain, which has been shown to have antimicrobial activity against many bacteria, both the collection strains and the antibiotic-resistant forms of clinical isolates of pathogenic bacteria and fungi. Considering this strain as an antibiotic producer, a step-by-step mutagenic treatment was carried out in order to obtain a variant that consistently exhibits a certain high-level antibiotic activity. A mutant variant was obtained during the three stages of mutagenic treatment and selection; it effectively suppresses the growth of pathogenic staphylococci, including methicillin-resistant staphylococcus (MRSA).